Shoulder Fractures in Context Controversies in Orthopaedic Surgery - Brorson, Stig.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book offers comprehensive coverage of all relevant aspects of shoulder fractures, also known as fractures of the proximal humerus, with a special focus on existing controversies in their treatment. Throughout the volume the author outlines the development of the modern scientific understanding in the field and the increasing operative approach to these injuries throughout the 20th century. The volume is subdivided into 5 sections, the first of which introduces shoulder fractures, their morphology and epidemiology. The second one presents their history, from the earliest known medical text in ancient Egypt to the mid-twentieth century. In the third part, the author discusses the challenges implied in understanding and translating$1 (Bfracture patterns into hierarchies and classification systems. Based on current clinical studies, the last part casts new light on the existing tension between an increasing interest in surgical procedures and implants, and the failure of emerging empirical evidence to demonstrate an added value for the vast majority of patients. In the book$1 (Bs conclusions, elaborating on this evidence, the author shares his reflections on the changing approaches to shoulder fractures and interprets them within a broader context of intellectual history. This book appeals a broad readership, including orthopaedic surgery residents, orthopaedic upper limb surgeons, medical decision-makers, medical historians, and those with an interest in the history and philosophy of medicine. This is an open access book.s
Part 1: What is a shoulder fracture? -- 1. Shoulder Fractures: A Brief Guide to Terminology -- 2. The Epidemiology of Shoulder Fractures -- 3. The Morphology of Shoulder Fractures: An Iconography -- . Part 2: History: shoulder fractures from ancient Egypt to 1950 -- 4. Pre-Radiological Diagnostics and Classification of Shoulder Fractures -- 5. Interventions for Shoulder Fractures from Ancient Egypt to the Eighteenth Century -- 6. Pathoanatomical Conceptions of Shoulder Fractures in the Nineteenth Century -- 7. Radiology and the Advent of Surgical Interventions for Shoulder Fractures -- . Part 3: Knowing and Telling a Fracture -- 8. Why Do We Classify Shoulder Fractures? -- 9. Imaging-Based Shoulder Fracture Classification Systems -- 10. Why Do We Disagree When Classifying Shoulder Fractures? -- 11. Interventions for Shoulder Fractures: The Evidence-Base -- 12. The Rise and Fall of an Implant: Locking Plates in Shoulder Fractures -- . Part 4: Eminence meets Evidence -- 13. The Use of Reverse Shoulder Arthroplasty in Shoulder Fractures -- 14. Outcome after Shoulder Fractures -- 15. Complications After Shoulder Fractures -- 16. Bridging the Evidence-Practice Gap in Shoulder Fracture Management -- . Part 5: Conclusion -- . Shoulder Fractures in Context: The Academic Bonesetter.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Orthopedic surgery; Radiology; Surgical Orthopedics; Radiology